IMPLEMENTASI PROGRAM RENCANA PEMBANGUNAN JANGKA MENENGAH DAERAH (RPJMD) KABUPATEN KUTAI BARAT TAHUN 2011 - 2015 - Frans Christiyanto (Jurnal Administrative Reform, 2019)
The purpose of this paper is to analyze the effect of variable communication, resources, disposition and organizational structure for program implementation RPJMD West Kutai 2011-2015, either partially or simultaneously. Type of this research is quantitative research. The analysis tool used is multiple linear regression. In this study using survey methods explanation (explanatory survey method) is a survey that explains the variables under study and further analyze the influence between variables accompanied by hypothesis testing. This research was conducted by collecting qualitative data, which will then be presented in the form of numbers (quantified) to be tested in accordance with the design verification of data analysis. The results showed the coefficient of determination (R2) of 0.421. There is significant influence between independent variables namely communication, resources, disposition and organizational structure for program implementation RPJMD West Kutai 2011-2015.Keyword: Implementation RPJMD, Communication, Resources